Pengaruh Penerapan Strategi Inquiring Minds Want To Know Terhadap Hasil Belajar Siswa - Af’idatun Nisaul Khoiroh; Imas Kania Rahman; Suhendra Suhendra (Al-Aulad: Journal of Islamic Primary Education, 2018)
This research aims to determine whether there are differences in student learning outcomes that use learning with inquiring minds want to know strategy and students who use conventional learning lectures. The research method used is Quasi Experimental Design with non-equivalent kontrol group design.The research sample is class 3C as many as 25 students as an experimental class and 3D class as many as 25 students as a kontrol class. Data collection techniques using a test, which consist of pretest and posttest questions.  Data analysis using Independent Sample tTest with t count obtained in the Independent sample t-Test is 2,932. Whereas the t table for the 5% significance level is 2.02 and 1% is 2.69, it can be seen that t count is greater than t table that is 2.02 <2.932> 2.69, meaning that there are differences in learning outcomes between experimental and kontrol classes. So it can be said that the Inquiring Minds Want to know Strategy influences student learning outcomes on “Money type and use” material.